Pengaruh Pendidikan, Pengalaman Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan di BPRS Amanah Rabbaniah Banjaran - Neng Esa Sayidah Maesaroh; Adi Indradi Wazdi; Yudhy Yudhy; Elan Rusnendar (Jurnal Dimamu, 2022)
The study aims to find out the effect of education, experience of work and environment of work on employee performance at BPRS Amanah Rabbaniah Banjaran either partially or simultaneously. The object of this study is the performance of employees at BPRS Amanah Rabbaniah Banjaran. As for the type of study that is quantitative associative. The type of data in this study is primary data, and the data collection techniques in the form of observations, interviews, literature studies, and questionnaires. Population of 62 people. While the sample used was purposive sampling with the determination of the sample using the slovin formula as many as 54 people. The result of this study indicate that education has a significant effect on employee performance where the value of tcount > ttable (5,696 > 2,008), experience of work does not significantly affect employee performance where the value of tcount < ttable (0,996 < 2,008), environment of work has a significant effect on employee performance where the value of tcount > ttable (5,381 > 2,008), simultaneously education, experience of work and environment of work significantly effect on employee performance where Fcount > Ftable (15,256 > 2,79).